Association of the Risk of Primary Sjögren's Syndrome With Fibrocystic Breast Disease: A Nationwide, Population-Based Study - Chen, Hsin-Hua; Chen, Hsian-Min; Lin, Ching-Heng; Tang, Kuo-Tung; Chen, Der-Yuan; Wei, James Cheng-Chung; Chao, Wen-Cheng (Frontiers in Medicine, 2021)
Objective: Primary Sjögren’s syndrome (pSS) is characterised by exocrine glandular inflammation; however, the association between preceding mammary-gland-inflammation-related diseases and newly diagnosed pSS remains unexplored. Methods: We used the 2003–2013 data retrieved from Taiwan’s National Health Insurance Research Database to conduct the present population-based study. We identified newly diagnosed pSS female patients during the 2001–2013 period, as well as age-matched (1:20) and propensity-score-matched (1:2) non-SS individuals (as controls). We explored the associations between pSS and a history of mastitis and fibrocystic breast disease by determining adjusted odds ratios (aORs) with 95% confidence intervals (CIs) using a conditional logistical regression analysis after controlling for potential confounders. Results: We identified 9,665 patients with pSS and 193,300 age-matched non-SS controls, as well as 9,155 SS cases and 18,310 propensity-score-matched non-SS controls. We found that fibrocystic breast disease (aOR, 1.75; 95% CI, 1.63–1.88) were independently associated with incident SS, whereas mastitis and childbirth-associated breast infections were not associated with incident SS. We also found positive associations between SS and previously reported SS-associated diseases, including cardiovascular diseases, thyroid diseases, pancreatitis, bronchiectasis, infectious diseases, osteoporosis and ankylosing spondylitis. In the propensity-score-matched populations, the associations between pSS and fibrocystic breast disease (aOR, 1.74; 95% CI, 1.58–1.91) remained consistent. Conclusion: The present population-based study revealed a previously unexplored association between pSS and history of fibrocystic breast disease, and the finding highlights the need to survey pSS in patients with mammary-gland-inflammation-associated diseases.